Fairness: A Critique to the Utilitarian Approach - Philipp Kircher; Alvaro Sandroni; Sandra Ludwig (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We address a basic diffculty with incorporating fairness into standard utilitarian choice theories. Standard utilitarian theories evaluate lotteries according to the (weighted) utility over ?nal outcomes and assume in particular that a lottery is never preferred over getting the most preferred underlying outcome with ertainty. While nearly universally adopted in economics (including behavioral economics) and appealing for choices among consumption goods, this approach is problematic when choices directly affect the payoffs of other individuals. A difficulty is that randomization may in itself be valued as a desirable procedure for allocating scarce resources. We highlight this in two simple choice settings. Individuals can choose between three options: to get more money; to get less money and someo ther good; to flip a coin between these two alternatives. When the good is a regular consumption good like a coffeemug, hardly any of our subjects randomize. When the good is a social good that yields payoffs directly to some other individual,nearly a third of our subjects choose to randomize. Our results indicate that fairness concerns are conducive to behavioral anomalies that the standard utilitarian model cannot accommodate.
urn:nbn:de:bvb:19-epub-13266-6
Keywords: D81; C91; D63; 330; risky choice; betweenness axiom; social preferences; preference for randomness